Reconfigurable homochiral colloidal clusters assembled under orthogonally applied electric and magnetic fields - Xingrui Zhu; Yuanxing Zhang; Benjamin L. Hanson; David T. Wu; Ning Wu (Proceedings of the National Academy of Sciences, 2025)
Chiral structures assembled from colloids are of great interest for applications in metamaterials and micromachines. However, similar to their molecular counterparts, these assemblies often result in racemic mixtures. Achieving homochirality by breaking the symmetry remains a significant challenge. Here, we report an approach to obtain single-handed clusters from colloidal dimers using orthogonal electric and magnetic fields. Applying an alternating-current electric field perpendicular to the substrate generates a mixture of chiral clusters with both handedness. However, symmetry is broken by superimposing a planar rotating magnetic field, favoring one chirality over the other. The cluster’s chirality can be precisely controlled in situ by adjusting the magnetic field’s direction and strength, as well as the electric field frequency. Remarkably, this method also induces uniform chirality in initially achiral clusters when exposed solely to the electric field. Both experimental and numerical analyses reveal that the stability of specific handedness depends on the competition between forces and torques generated by the magnetic field, electric field, and electrohydrodynamic flow. Furthermore, we propose a strategy for producing colloidal clusters with uniform sizes and single-handedness through dynamic tuning of the electric and magnetic fields. This work not only demonstrates the potential of integrating external fields but also provides a viable way to create reconfigurable chiral colloidal structures.